2017
DOI: 10.1016/j.jadohealth.2017.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Cessation of Injecting and Preceding Drug Use Patterns Among a Prospective Cohort of Street-Involved Youth

Abstract: Purpose Injection drug use is prevalent among street-involved youth, but patterns of cessation are poorly described. We identified drug use patterns preceding injection cessation among street-involved youth. Methods From September 2005 to May 2015, we collected data from the At-Risk Youth Study, a prospective cohort of street-involved youth in Vancouver, Canada, and limited the sample to actively injecting youth. The primary outcome was cessation of injecting self-reported at semiannual follow-up visits. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…A growing number of prospective cohort studies have examined short-term IDU cessation (commonly defined as reporting no IDU for six or twelve months), with cessation incidence rates ranging from 4.1 to 32.6 per 100 person-years (PY) (Evans et al, 2009; Genberg et al, 2011a; Langendam et al, 2000; Nambiar et al, 2015; Shah et al, 2006; Steensma et al, 2005). Factors positively associated with IDU cessation have included younger age, being employed (Huo et al, 2006; Luchenski et al, 2015; Nambiar et al, 2015; Shah et al, 2006; Steensma et al, 2005) lower frequency of IDU, engagement in drug treatment, particularly opioid substitution treatment (OST), and reporting a previous cessation (DeBeck et al, 2011; Evans et al, 2009; Hadland et al, 2017; Huo et al, 2006; Langendam et al, 2000; Shah et al, 2006; Steensma et al, 2005; Werb et al, 2013; Xia et al, 2015). Conversely, homelessness, residing in a disadvantaged neighbourhood, incarceration, and alcohol and non-injection drug use have been inversely associated with IDU cessation (Bruneau et al, 2004; Evans et al, 2009; Genberg et al, 2011a; Hadland et al, 2017; Kimber et al, 2010; Luchenski et al, 2015; Nambiar et al, 2015; Shah et al, 2006; Steensma et al, 2005; Werb et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of prospective cohort studies have examined short-term IDU cessation (commonly defined as reporting no IDU for six or twelve months), with cessation incidence rates ranging from 4.1 to 32.6 per 100 person-years (PY) (Evans et al, 2009; Genberg et al, 2011a; Langendam et al, 2000; Nambiar et al, 2015; Shah et al, 2006; Steensma et al, 2005). Factors positively associated with IDU cessation have included younger age, being employed (Huo et al, 2006; Luchenski et al, 2015; Nambiar et al, 2015; Shah et al, 2006; Steensma et al, 2005) lower frequency of IDU, engagement in drug treatment, particularly opioid substitution treatment (OST), and reporting a previous cessation (DeBeck et al, 2011; Evans et al, 2009; Hadland et al, 2017; Huo et al, 2006; Langendam et al, 2000; Shah et al, 2006; Steensma et al, 2005; Werb et al, 2013; Xia et al, 2015). Conversely, homelessness, residing in a disadvantaged neighbourhood, incarceration, and alcohol and non-injection drug use have been inversely associated with IDU cessation (Bruneau et al, 2004; Evans et al, 2009; Genberg et al, 2011a; Hadland et al, 2017; Kimber et al, 2010; Luchenski et al, 2015; Nambiar et al, 2015; Shah et al, 2006; Steensma et al, 2005; Werb et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The existing research on VH risk supports that youth from low-income, vulnerable backgrounds are at the greatest risk of infection; yet, prevention research and programming is minimal. Those studies that are available on VH knowledge have focused largely on homeless [21][22] and injecting drug using U.S. youth [23][24][25][26][27]. While these are highly critical populations, there is a need for research examining VH risk and knowledge among low-income ethnic minority youth, in general.…”
Section: Viral Hepatitis and Youthmentioning
confidence: 99%
“…Several studies noted that those who recently participated in drug detoxification, residential treatment, methadone maintenance, and 12-step programs (Evans et al, 2009), and specifically methadone maintenance (Horyniak et al, 2018;Nambiar et al, 2015), were more likely to cease injection drug use. However, one study reported that participation in methadone maintenance, outpatient treatment, residential treatment, Narcotics' Anonymous, or detoxification was not associated with cessation of injection drug use -likely due to limited access (Hadland, Wood, Nosova, Kerr, & DeBeck, 2017) and another reported that abstinence-based treatment methods like 12-step programs impeded injection cessation efforts (Boyd, Fast, Hobbins, McNeil, & Small, 2017). There have also been mixed findings with respect to the direction of the association between injection drug use cessation and recent arrest (Hadland et al, 2017;Horyniak et al, 2018;Nambiar et al, 2015), and incarceration (Deren et al, 2007;Mehta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%